De exclusão a limitações digitais: condições sociodemográficas, habilidades, atitudes e uso da Internet. - Mota, Flavio Perazzo Barbosa (2016)
The purpose of this thesis dissertation was to study how skills, attitudes and sociodemographic conditions contribute do Internet use. In order to do that, we conducted three specific studies. First (chapter 2) we explored the relationship among gender, age, education and Internet use (level, types and non-use). Through a literature review and secondary data provided by the Information and Communication Technology Research Institute (CETIC.br) it was possible to: (a) verify that these sociodemografic conditions represent an incomplete source to understand Internet use; and (b) identify the necessity of studying cognition factors (in particular, skills and attitudes). In the second study (chapter 3), we tried to understand how these two factor are defined, measured and relate to sociodemographic conditions studied. Through two mapping studies it was possible to: (a) identify two main frameworks (operational, formal, information and strategic skills; terminological knowledge) that guide Internet skills research, and that although they have the objective of studying the same concept, they possess characteristics, sophistication and distinct range; (b) systemize the attitudinal concept in two dimensions (cognition and affection) as a start point to refine and deep understand of its role on Internet effective use (for now on strategic skills); and (c) establish three propositions to further verification. In the third study (chapter 4), we explored the relationship among gender, age, education, Internet skills and attitudes. Through primary data, first we adapted and validated scales to measure the constructs. Then, by estimating linear regression models (parametric and non-parametrics) it was possible to verify that information skills and perceived appreciation (curiosity, interest and satisfaction) were the main predictor of strategic skills. Taking together the results of the three studies conducted, they contributed to reach the proposed objective and develop the thesis argument. That is, through a multidisciplinary, integrated and emergent approach we verified that attitudes and skills are intricate elements to understand internet use.